Assumed jurisdiction in Canada: identifying and interpreting presumptive connecting factors - Pitel, Stephen G.A.; Black, Vaughan (Journal of Private International Law, 2018)
The common law of assumed jurisdiction in Canada now consists of judges interpreting and applying the presumptive connecting factors established for tort claims in Club Resorts Ltd. v Van Breda and identifying and fleshing out the contours of presumptive connecting factors for claims other than tort. There is a pressing need for detailed analysis. While the presumptive connecting factor of a tort committed in the forum has been easy to apply in some cases, such as motor vehicle collisions, it has been much harder to apply in cases of defamation, misrepresentation, deceit and conspiracy. Beyond tort, presumptive connecting factors for certain causes of action such as breach of fiduciary duty, breach of confidence, or reversal of an unjust enrichment remain under-analysed. Little consensus exists on what aspects, if any, of these claims would constitute a sufficient connection for assumed jurisdiction. There are also important questions about how the presumptive connecting factor approach operates for several federal and provincial statutory causes of action, which differ in important ways from common law claims, and for assumed jurisdiction with respect to concurrent claims.
QID: Q129295763